Distinguishing coercion and underspecification in Type Composition Logic - Lukassek, Julia; Spalek, Alexandra Anna (Proceedings of Sinn und Bedeutung, 2019)
This paper investigates the meaning adaptability of change of state (CoS) verbs. It argues that both coercion and underspecification are necessary mechanisms in order to properly account for the semantic adaptability observable for CoS verbs in combination with their complements. This type of meaning adaptability has received little formal attention to date, although some recent work has already led the way on this topic (Spalek, 2014; Lukassek and Spalek, 2016; Asher et al., 2017). Our paper is part of a cross-linguistic case study of German einfrieren and Spanish congelar (‘freeze’). We model the meaning adaptability of this test case within Type Composition Logic (TCL) (Asher, 2011). We build on Asher’s coercion mechanism and introduce an additional mechanism for underspecification that exploits the fine-grained type system in TCL.